CRYSTAL STRUCTURE STUDY OF A MIXED LIGAND COMPLEX OF SPIRIT ACETATE WITH 2-AMINO-5-MERCAPTO-1,3,4-THIADIAZOLE AND ETHYLENEDIAMINE (The New Uzbekistan Journal of Medicine, 2025)
In this work, a synthesis method based on the oxidation-reduction reaction of a new 1,3,4-thiadiazole derivative is presented. The structure of the obtained new organic substance was proven by infrared spectroscopy and X-ray structure analysis.